Target-dependent plasticity of galanin and vasoactive intestinal peptide in the rat superior cervical ganglion after nerve lesion and re-innervation - Klimaschewski, Lars Peter; Grohmann, Inga; Heym, Christine (Neuroscience, 1996)
The expression of the neuropeptides galanin and vasoactive intestinal peptide (VIP) is increased in subpopulations of sympathetic neurons after axotomy of the rat superior cervical ganglion. We investigated whether postganglionic neurons innervating different targets show a prevalence for any of the two peptides in response to carotid nerve lesion. Before the respective postganglionic axons were crushed close to the ganglion, postganglionic neurons projecting either to the iris (through the internal carotid nerve) or to the submandibular gland (through both carotid branches) were identified by the retrograde tracer Fast Blue. Galanin and VIP immunoreactivities were demonstrated two and 30 days after crush and after successful regeneration of the lesioned neurons (60 days). In control ganglia, both peptides were detected in a few gland- but not in iris-projecting neurons. However, two days after crush of the respective carotid nerves, 14% of neurons within the iris and 46% within the gland population were immunoreactive for galanin. The percentage of neurons immunoreactive for VIP was significantly lower in both populations: only 3.5% of neurons projecting to the iris and 23% of the gland-projecting neuron population exhibited this peptide. After 30 days, the percentage of galanin- and VIP-positive neurons projecting to the submandibular gland was reduced (24% and 5.7%, respectively), whereas the proportion of galanin-immunoreactive neurons further increased within the iris population (55%), indicating that some neurons express galanin at later stages after the lesion. At 60 days after the crush, the percentage of galanin- or VIP-immunoreactive neurons had decreased to control levels within those neuron populations that re-innervated the iris or submandibular gland, although the total number of neurons exhibiting galanin or VIP was still increased within the ganglion, suggesting that re-establishment of target contact may play a role in down-regulation of both peptides.
Elektronische Reproduktion der Druck-Ausgabe 2. März 1999
Gesehen am 06.11.2205